CFD INVESTIGATION OF THE PRESSURE DISTRIBUTION IN CENTRIFUGAL VORTEX IMPELLERS - Mihalić, Tihomir; Predin, Andrej; Mustapić, Nenad (Journal of Energy Technology, 2024)
A Computational Fluids Dynamics (CFD) analysis of the pressure fields in a centrifugal vortex impeller was undertaken in this paper. The aim was to increase pressure distribution along the impeller blades to determine whether a vortex impeller added to the centrifugal impeller can delay the start of cavitation. The calculating domain was mesh by finite control volumes, and equations were solved with ANSYS FLUENT 14. Furthermore, the measurement results were used as experimental validation of numerical simulations. This validation was done by taking pressure measurements at some locations in experimental models, and comparing them with those obtained with CFD simulations. It was shown that the centrifugal vortex impeller generates higher pressure in critical areas along the blades than the centrifugal impeller does for the same head.